Economic indicators of the production of important fruit-specific species in Vojvodina - Lukač-Bulatović Mirjana; Vukoje Veljko; Milić Dušan (Ekonomika Poljoprivrede (1979), 2017)
The paper discusses the basic economic and production results of important fruit species (apple, pear, peach, sour cherry and plum) on agricultural farms of Vojvodina. The aim of the research is to evaluate the most important parameters of cost-effectiveness of these productions, and propose measures to improve the existing situation. Comparative analysis clearly shows that the most cost-effective is pears production, followed by apple, cherry, peach and plum. Pear production gives the largest coverage margin per unit capacity (1,261,786 din /ha), which is 16.5% better than in apple production (1,083,160 din /ha), or about 7.8 times better in relation to plums production (161,796 din /ha). The highest coefficient of economy (3.19) is, also, recorded in the production of pear (for apples 2.94, cherry 2.27, peach 2.17 and plum 1.44). Further development of fruit production in Vojvodina involves raising intensive farms with quality fruit varieties, firmer vertical linking of producers and processors, ensurement of economic safety of producers in the long run, making of fruit producing regions, etc.